2008
DOI: 10.1093/bib/bbn001
|View full text |Cite
|
Sign up to set email alerts
|

Gene-set approach for expression pattern analysis

Abstract: Recently developed gene set analysis methods evaluate differential expression patterns of gene groups instead of those of individual genes. This approach especially targets gene groups whose constituents show subtle but coordinated expression changes, which might not be detected by the usual individual gene analysis. The approach has been quite successful in deriving new information from expression data, and a number of methods and tools have been developed intensively in recent years. We review those methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
228
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(231 citation statements)
references
References 47 publications
0
228
0
3
Order By: Relevance
“…Well-known examples include the gene set enrichment analysis [41] and the maxmean approach [42]. The reader is referred to [43,44] for comprehensive reviews of existing approaches on gene set analysis. Here we highlight the fact that gene set significance testing is different from pathway-guided biomarker discovery since they have different objectives.…”
Section: Knowledge-driven Group Formationmentioning
confidence: 99%
“…Well-known examples include the gene set enrichment analysis [41] and the maxmean approach [42]. The reader is referred to [43,44] for comprehensive reviews of existing approaches on gene set analysis. Here we highlight the fact that gene set significance testing is different from pathway-guided biomarker discovery since they have different objectives.…”
Section: Knowledge-driven Group Formationmentioning
confidence: 99%
“…Numerous genome-wide gene expression analyses have shown that single-gene analysis can find little similarity between two independent studies, but pathway-based analysis may find a number of pathways in common. 24 A pathway analysis is done to identify pathways that are significantly associated with the disease. In other words, we attempt to test whether the pathway is overrepresented by the genes that are significantly associated with the disease.…”
Section: Resultsmentioning
confidence: 99%
“…There are two primary types of gene function enrichment analysis methods, individual gene analysis (IGA) and gene set analysis (GSA). [1][2][3] IGA identifies differentially expressed genes through a variety of methods and tests the difference of the proportion of differentially expressed genes between all genes and a given gene set. 4,5 GSA directly calculates gene subset scores using various statistical methods and calculates the significance level.…”
Section: Introductionmentioning
confidence: 99%